2017
DOI: 10.1007/s10709-017-9974-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of DNA methylation on EEF1D and RPL8 expression in cattle

Abstract: Dynamic changes to the epigenome play a critical role in a variety of biology processes and complex traits. Many important candidate genes have been identified through our previous genome wide association study (GWAS) on milk production traits in dairy cattle. However, the underlying mechanism of candidate genes have not yet been clearly understood. In this study, we analyzed the methylation variation of the candidate genes, EEF1D and RPL8, which were identified to be strongly associated with milk production t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Mechanisms of epigenetic gene regulation function through the modulation of chromatin structure, and may either repress or enhance gene expression. It has been reported that milk proteins are in fact influenced by DNA methylation ( Nguyen et al, 2014 ; Liu et al, 2017 ), histone modifications, such as acetylation, ubiquitination, and phosphorylation ( Wang et al, 2017 ), and microRNAs ( Li R. et al, 2016 ; Wang et al, 2016 ). However, a new epigenetic component – long non-coding RNAs (lncRNAs), which were recently demonstrated to be critical gene regulators of cellular metabolism ( Zhao and Lin, 2015 ), are yet to be thoroughly examined.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms of epigenetic gene regulation function through the modulation of chromatin structure, and may either repress or enhance gene expression. It has been reported that milk proteins are in fact influenced by DNA methylation ( Nguyen et al, 2014 ; Liu et al, 2017 ), histone modifications, such as acetylation, ubiquitination, and phosphorylation ( Wang et al, 2017 ), and microRNAs ( Li R. et al, 2016 ; Wang et al, 2016 ). However, a new epigenetic component – long non-coding RNAs (lncRNAs), which were recently demonstrated to be critical gene regulators of cellular metabolism ( Zhao and Lin, 2015 ), are yet to be thoroughly examined.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al 2010;Nayeri et al 2017). In addition to DGAT1, 20 more positional candidate genes were identified underlying this QTL (Table 1) that have been previously associated with milk production (Jiang et al 2014;Capomaccio et al 2015;Nayeri et al 2016;Suchocki et al 2016;Liu et al 2017;Sanchez et al 2017). This is the first time that the remaining four positional candidate genes (KIFC2, MFSD3, LRRC24 and SLC39A4) have been associated with 305MY, although they have recently been associated with milk fatty acid composition in Italian Simmental and Italian Holstein cattle (Palombo et al 2018).…”
Section: Author Manuscriptmentioning
confidence: 88%
“…Besides the canonical role of EEF1D as a direct substrate for casein kinase 2 (CK2), an important regulator of cell cycle progression, apoptosis, and transcription [ 21 , 22 ], EEF1D, could also participate in autoubiquitination and degradation by interacting with SIAH E3 ubiquitin protein ligase 1 (SIAH-1) [ 23 ]. Several researchers reported that gene amplification, genetic methylation, and posttranslational modification may play a role in the mechanisms of EEF1 superfamily proteins in different cancers [ 24 ].…”
Section: Discussionmentioning
confidence: 99%